The content of the «social literacy» concept in pedagogical theory and practice - O. E. Sirotkin (Вестник Майкопского государственного технологического университета)
Scientific research in recent years has documented a violation of the mechanism for the inclusion of young citizens in adulthood and the dominance of consumer attitudes among modern youth. It is quite obvious that one of the indicators of civil society is the desire of people to be its full members, responsible and capable of socially useful activities. The ongoing change in the geopolitical situation in the world has particularly acutely actualized the problem of children and adolescents developing social literacy as a special criterion for the development of society.   The need to solve this issue determined the research problem, which lies in the insufficient knowledge of the content of social literacy of children and adolescents in modern pedagogical discourse and the demand for a theoretical justification of this term from the standpoint of the modern sociocultural situation.   Accordingly, the purpose of this research is to reveal the concept of “social literacy” in pedagogical theory and practice.   The research methods used in the work are the following: analysis of teaching experience and theoretical approaches to the problem under study, synthesis, differentiation, methods of visual presentation of the data obtained.   The results of the research. The content of social literacy in pedagogical scientific and scientific-methodological research has been revealed; components of social literacy have been proposed.   Key conclusions: social literacy is understood as an individual’s readiness to socialize safely in the environment; possession of an interdependent set of knowledge, skills and abilities, as well as the necessary personal qualities that ensure the formation of this readiness; social literacy includes a set of interrelated components: personal, activity and reflexive, identified on the basis of systematization of axiological, environmental, competence and multi-subjective approaches.